(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigates the effect of different sowing media and soil amendments on seed germination and early seedling growth of Pterocarpus osun. The study was carried out at the nursery site of the Department of Forest Resources and Wildlife Management, Ekiti State University, Ado-Ekiti. Sixty seeds were sown in plastic bowls filled with the different sowing media (sawdust, river sand, and topsoil). Watering was done twice daily, while seed germination was monitored for four weeks. The number of seeds germinated per day was recorded for each treatment till no further germination was observed. For the growth experiment, seedlings with relatively uniform height were selected and transplanted into polythene pots filled with topsoil amended with different organic manure (poultry dropping, cow dung, poultry dropping + cow dung). The treatments were replicated ten (10) times. Growth parameters viz; (heights, stem diameter, and number of leaves) were measured over 12 weeks. The study revealed that seeds sown in sawdust had the lowest mean germination time (MGT) of 19.93 days. Time spread of germination (TSG) shows that seeds sown in river sand had the longest germination circle of 12 days. While seeds sown in sawdust had the highest germination percentage (GP) of 96.65 %. The result revealed that seedlings grown on soil amended with cow dung performed best for all the parameters measured throughout the growth period. It is recommended that sawdust should be adopted for germination of Pterocarpus osun and cow dung should be used as organic manure for raising the seedlings in the nursery.